Financial stress in emerging adults with type 1 diabetes: a mini review integrating lessons from cancer research - Wentzell, Katherine; Nagel, Kathryn E. (Frontiers in Clinical Diabetes and Healthcare, 2024)
Amongst adults in the United States, those ages 18-30 have the highest unemployment rates, the lowest incomes, and are the most likely to be uninsured. Achieving financial independence is a core developmental task for this age group, but for those with type 1 diabetes (T1D), the high costs of insulin and diabetes supplies as well as an employment-based insurance model with minimal safety net can make this a formidable challenge. Cost-related non-adherence to diabetes management is particularly high in emerging adults with T1D and is associated with severe consequences, such as diabetic ketoacidosis (DKA) and even death. Objective financial burden and subjective financial distress related to illness are not unique to diabetes; in cancer care this construct is termed financial toxicity. Researchers have identified that emerging adults with cancer are particularly vulnerable to financial toxicity. Such research has helped inform models of care for cancer patients to mitigate cost-related stress. This mini review aims to briefly describe the state of the science on financial stress for emerging adults with T1D and explore parallels in cancer scholarship that can help guide future work in diabetes care to reduce health inequity, drive research forward, improve clinical care, and inform policy debates.